2017
DOI: 10.3329/jesnr.v10i1.34686
|View full text |Cite
|
Sign up to set email alerts
|

A Nondestructive Method to Estimate Plant Height, Stem Diameter and Biomass of Rice under Field Conditions Using Digital Image Analysis

Abstract: Plant phenotyping intends measuring complex plant traits, and is important in agricultural research for enhancing yield improvement. Manual plant phenotyping is laborious and destructive, and hence a less-laborious and non-destructive method is required. Here, we proposed a nondestructive method to estimate continuous data of plant traits such as height, stem diameter and biomass using a low cost time-lapse camera. The camera was installed at a rice field in Japan, and captured images for four target plants ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The additional information about the canopy architecture can then be integrated into the modelling of yield formation and biomass and has the potential to improve the models [28,48]. On the one hand, many authors reported that RGB indices outperform spectroradiometric VIs in terms of characterizing plant growth [49][50][51], separating vegetation from bare soil [52], assessing nitrogen [27,53] and detecting foliar diseases [54,55]. This could be in part due to the fact that spectroradiometric indices exhibit longer wavelengths in the NIR range than RGB indices and are thus more susceptible to canopy architecture, which affects the reflective properties of plants, and soil mixing pixels, which occurs especially at low spatial resolution [56].…”
Section: Introductionmentioning
confidence: 99%
“…The additional information about the canopy architecture can then be integrated into the modelling of yield formation and biomass and has the potential to improve the models [28,48]. On the one hand, many authors reported that RGB indices outperform spectroradiometric VIs in terms of characterizing plant growth [49][50][51], separating vegetation from bare soil [52], assessing nitrogen [27,53] and detecting foliar diseases [54,55]. This could be in part due to the fact that spectroradiometric indices exhibit longer wavelengths in the NIR range than RGB indices and are thus more susceptible to canopy architecture, which affects the reflective properties of plants, and soil mixing pixels, which occurs especially at low spatial resolution [56].…”
Section: Introductionmentioning
confidence: 99%